CLINICAL CHARACTERISTICS OF PATIENTS WITH CHRONIC FATIGUE SYNDROME - Remzi Çevik; Ali Gür; Kemal Nas; Suat Acar; A. Jale Saraç (Archives of Rheumatology, 2003)
Purpose: Chronic fatigue syndrome (CFS) consists of a range of symptoms including fatigue, headache, sleep disturbances, difficulties in concentration, and muscle pain. Our aim was to describe the clinical and demographical features of the patients with CFS and to compare them with the control group. Methods. Sixty-eight women with CFS (mean age: 31±8) and 52 healthy women (mean age: 29±6) were included in the study. Clinical findings and demographical data of the patients with CFS were evaluated and compared with control group. Results: Most commonly detected symptoms were fatigue (100%), myalgia (97%), adenopathy (87%), pharyngitis (84%), arthralgia (84%), sleep disturbances (73.5%) and sore throat (69%) in women with CFS. Depression level and tender point count were higher than controls. Conclusions: These data demonstrate that depression level is higher, and fatigue, myalgia, adenopathy, sore throat, and athralgia are the most commonly symptoms that occurred in patients with CFS. In addition CFS should be taken into consideration in patients with such complaints for long time.